PENGARUH GAME CLASH OF CHAMPIONS TERHADAP EFEKTIVITAS EVALUASI PEMBELAJARAN PAI MENGENAI ULAMA INDONESIA - Fakhri, Ahmad; Hamzah, Arif (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2026)
This study aims to determine the effectiveness of the Clash of Champions game as an evaluation method in Islamic Religious Education learning on the topic of Indonesian ulama. This research used a quantitative approach with an experimental method employing a one-group pretest–posttest design. The research sample consisted of 27 students of class XI-G at SMA Negeri 74 Jakarta. Data were collected through pretest and posttest instruments and analyzed using descriptive statistics, normality tests, N-Gain tests, and paired sample t-tests with the assistance of IBM SPSS software. The results showed that the average pretest score was 52.22 while the average posttest score increased to 75.74. The N-Gain value obtained was 0.51 which falls into the moderately effective category. The paired sample t-test analysis showed a significance value of 0.000 < 0.05, indicating a significant difference between pretest and posttest results. These findings indicate that the Clash of Champions game is effective as an alternative evaluation method to improve students’ learning outcomes and engagement in Islamic Religious Education learning.